Improve the salinity stress by using ascorbic acid on Germination, Growth Parameters, Water Relations, Organic and Inorganic Components of Sweet Pepper (Capsicum annuum, L.) Plant - Al Othaimen, Hanan Saleh (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
The relationship between compatible solutes (osmolytes) and antioxidants are the strategies that plants have developed to tolerate salt stress. A greenhouse experiment was carried out to study the response of presoaked Sweet Peppers (Capsicum annuum, L.) seeds in freshly prepared ascorbic acid (25 mML-1 ASC) or distilled water (control) for 12 h at natural environmental conditions, to reduce the effect of salinity stress. Generally, the sweet pepper seeds germination occurred after 4 days, while, the germination rate (%) were more faster after soaking the seeds in ascorbic acid compared with control (soaked in distilled water). NaCl salt-stress treatments caused a reduction in all growth parameters (fresh and dry weights of plant, leaf area and number per plant) compared control, particularly at high NaCl level (250 mM) more reduced. In the mean time, ascorbic acid had reduced the effect NaCl salinity stress on all growth parameters. Photosynthetic pigments (chlorophyll a & b and carotenoids) and chloroplast efficiency were increasing with salinity stress, but the response was more pronounced at 250 mM NaCl whether alone or combined with ascorbic acid. Also, salinity stress treatments tended to increased all of the total available carbohydrates (Monosaccharide, Disaccharides & polysaccharides), nitrogenous components (protein, amino acids & proline), antioxidase, (catalase, peroxidase & superoxide dismutases) enzymes activities and inorganic mineral elements (Na+, K+, N+3, P+3, Ca+2, Mg+2 & Cl-) but after soaked the seeds in ascorbic acid, these components tended to increased more. Application of NaCl salinity-stress on tomato plant induced the synthesis of nitrogenous components (protein, amino acids, proline), whereas, the tomato seeds soaked before planting in ascorbic acid which leads to remarkably increasing more for all nitrogenous components, antioxidase, carbohydrates and inorganic mineral elements content.